OVERVIEW OF MANAGEMENT PURSED LIPS BREATHING RESPIRATORY TECHNIQUES IN CHRONIC OBSTRUCTIVE LUNG DISEASE (COPD): SYSTEMATIC REVIEW - AMELIA NURUL HAKIM; M ADHARUDIN; NI BODRO ARDI; MUH FIRMAN YUDIATMA (NURSING ANALYSIS: Journal of Nursing Research, 2022)
ABSTRACT Background: Pursed Lip Breathing is a breathing technique that exhales through pursed lips (cones) and breathes through the nose with the mouth closed. This technique is used to relieve shortness of breath and improve breathing. Purpose of the study: To describe the management of pursed lip breathing breathing techniques in patients with chronic obstructive pulmonary disease. Methods: This systematic review was compiled using the databases of Google scholar, Sciencee Direct and Pubmed. Article selection is carried out to identify relevant articles and then screening is carried out to adjust to the inclusion criteria. There were 16 articles that met the inclusion criteria and were reviewed using JBI (Joanna Briggs Institute Levels). Results: The results showed that the data showed that the management of the pursed lip breathing technique was influenced by the pursed lip breathing method or technique. Keywords: Methods, Pursed Lip Breathing, COPD, Techniques  GAMBARAN PENATALAKSANAAN TEKNIK PERNAFASAN PURSED LIPS BREATHING PADA PENYAKIT PARU OBSTRUKTIF KRONIK (PPOK): TINJAUAN SISTEMATIS ABSTRAKLatar Belakang: Pursed Lip Breathing merupakan teknik pernapasan yang mengeluarkan napas melalui bibir yang mengerut (kerucut) dan bernapas melalui hidung dengan mulut tertutup. Teknik ini untuk meredakan sesak napa dan meningkatkan pernapasan. Tujuan penelitian: Untuk mengetahui gambaran penatalaksanaan teknik pernapasan pursed lip breathing pada pasien penyakit paru obstruktif kronik. Metode penelitian: Sistematic review ini disusun menggunakan database Google scholar, Scient direct dan Pubmed. Seleksi artikel dilakukan untuk mengidentifikasi artikel yang relevan kemudian dilakukan screening untuk menyesuaikan dengan kriteria inklusi. Didapatkan 16 artikel yang idapat sesuai kriteria inklusi dan direview menggunakan JBI (Joanna Briggs Institute Levels). Hasil: Hasil penelitian menunjukan bahwa data menunjukan bahsa penatalaksanaan pemberian teknik pernapasan pursed lip breathing dipengaruhi oleh metode atau tekni pernapasan pursed lip breathing. Kata kunci: Metode, Pursed Lip Breathing, PPOK, Teknik